1987
DOI: 10.1139/b87-347
|View full text |Cite
|
Sign up to set email alerts
|

The taxonomy of the Viola nuttallii complex

Abstract: 1987. The taxonomy of the Viola nuttallii complex. Can. J. Bot. 65: 2562 -2580.Morphological, cytological, and phytochemical data were incorporated into numerical and statistical analyses to produce a revision of Viola subsection Nuttallianae. A basic chromosome number of x = 6 was confirmed for this polyploid~complex, which includes five species: V. vallicola, 2n = 12; V. tomentosa, 2n = 12; V. nuttallii, 2n = 24; V. praemorsa, 2n = 36 and 48; and V. bakeri, 2n = 48. Departures from recent authors include the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…Both subsections are native to the more arid parts of western North America; subsection Chrysanthae consists of summer-dormant geophytes with deeply divided leaves and (with one exception) no cleistogamous fl owers, while subsection Nuttallianae are mostly chamaephytes with entire leaves and cleistogamous fl owers ( Table 1 ). A close relationship between these subsections had been proposed previously based on rDNA (ITS) sequences ( Ballard et al, 1998 ) and the occurrence of spontaneous hybrids ( Clausen, 1964 ), and Fabijan et al (1987) suggested, based on the expression of fl avonoid compounds, that these groups might…”
Section: Reticulate Phylogeny and Evolution Within Viola Sectionsupporting
confidence: 54%
See 2 more Smart Citations
“…Both subsections are native to the more arid parts of western North America; subsection Chrysanthae consists of summer-dormant geophytes with deeply divided leaves and (with one exception) no cleistogamous fl owers, while subsection Nuttallianae are mostly chamaephytes with entire leaves and cleistogamous fl owers ( Table 1 ). A close relationship between these subsections had been proposed previously based on rDNA (ITS) sequences ( Ballard et al, 1998 ) and the occurrence of spontaneous hybrids ( Clausen, 1964 ), and Fabijan et al (1987) suggested, based on the expression of fl avonoid compounds, that these groups might…”
Section: Reticulate Phylogeny and Evolution Within Viola Sectionsupporting
confidence: 54%
“…In the original description of V. guadalupensis , Powell and Wauer (1990) suggested an affi nity with subsection Nuttallianae (W. Becker) J. Clausen, a diploid-polyploid complex (2 x to 8 x ) endemic to central and western North America ( Stebbins et al, 1963 ;Clausen, 1964 ;Fabijan et al, 1987 ) and comprising 10 Ging. Section Chamaemelanium is expanded compared to Becker ' s (1925) original treatment and includes also subsection Orbiculares (previously section Nomimium Ging.)…”
Section: Establishing the Phylogenetic Origin History And Age Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…A second possible explanation is that C. grandiflora, an annual, has only one season to reproduce. The two species used in previous experimental studies of CH versus CL allocation under pollen limitation, V. pubescens and V. praemorsa, are both perennials (Fabijan et al 1987;Culley 2002). Annual plants are particularly likely to evolve strategies that maximize reproduction within one season because they cannot reallocate resources to future reproduction.…”
Section: Comparisons To Previous Observational and Experimental Studiesmentioning
confidence: 99%
“…is a widespread species in western North America, where it can grow at elevations up to 3500 m a.s.l. (Fabijan et al 1987). Populations at high elevations experience shorter growing seasons and are likely to be visited by different pollinators; these factors might be expected to drive differences in reproductive success or breeding system (Kudo 2006).…”
Section: Introductionmentioning
confidence: 99%